Literature, Theory, History - Hart, J. author. aut Link
XII, 265 p.
Keywords: This book discusses literature, theory and history in close relation. Its main focus is on comparative literature and history, culture, poetics, rhetoric, theatricality, genre and gender, and balances close reading with theory and historical context.